Synthesis, characterization and in vivo biological evaluation of novel benzimidazoles as potential anticancer agents - Roopashree, Rangaswamy; Mohan, Chakrabhavi Dhananjaya; Swaroop, Toreshettahally Ramesh; Jagadish, Swamy; RANGAPPA, KANCHUGARAKOPPAL SUBBEGOWDA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Cancer is one of the major cause of death worldwide irrespective of the sex. The aim of the study is to design, synthesize and identification of novel anti-proliferative agents that can potently target cancer. Methodology: We are reporting the synthesis of new series of N-substituted 2-(2-butyl-4-chloro-1H-imidazole-5-yl)-1H-benzo[d]imidazole derivatives and evaluated for their anti-tumor activity against HeLa cell lines. We identified the lead compound in the series and tested its anti-proliferative and anti-angiogenic properties against EAT bearing mice. Results: We identified 2-(2-butyl-4-chloro-1-heptyl-1H-imidazol-5yl)-1H-benzo[d]imidazole as a lead compound with the IC50 of 25.3 ÂµM. The lead compound is significantly decreases angiogenesis in peritoneum of EAT bearing mice. Conclusion: Our results clearly demonstrates that benzimidazoles suppresses the cell proliferation, peritoneal angiogenesis and ascites volume.